2016
DOI: 10.15835/nbha44110254
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation and Leaf Removal Effects on Polyphenolic Content of Grapes and Wines Produced from cv. ‘Agiorgitiko’ (<i>Vitis vinifera</i> L.)

Abstract: Vitis vinifera L. cv. 'Agiorgitiko' is one of the most important red grape varieties of Greece, cultivated almost exclusively in the region of Nemea in north-eastern Peloponnese. This work aimed to study the influence of some commonly applied viticultural practices on the polyphenolic composition of 'Agiorgitiko'. Leaf removal at veraison, irrigation, and a combination of both, were applied and the phenolic content of the grapes and of the produced wines was compared. The results showed that leaf removal decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 31 publications
(23 reference statements)
5
17
0
Order By: Relevance
“…The most beneficial effects are observed when water deficit occurs throughout ripening. Aside from an overall increase in the accumulation of phenylpropanoids and flavonoids (Chorti et al, 2016;Koundouras, 2018), several studies showed a modification in composition of anthocyanins toward a relative increase of tri-hydroxylated anthocyanins (3 ′ ,4 ′ ,5 ′hydroxylated: delphinidin, petunidin, malvidin) (Castellarin et al, 2007a;Ollé et al, 2011;Cook et al, 2015). However, the changes in the anthocyanin profile in response to water deficit appear to be highly varietal dependent (Niculcea et al, 2014;Theodorou et al, 2019).…”
Section: Water Impact Of Vine Water Status On Phenolic Compoundsmentioning
confidence: 99%
“…The most beneficial effects are observed when water deficit occurs throughout ripening. Aside from an overall increase in the accumulation of phenylpropanoids and flavonoids (Chorti et al, 2016;Koundouras, 2018), several studies showed a modification in composition of anthocyanins toward a relative increase of tri-hydroxylated anthocyanins (3 ′ ,4 ′ ,5 ′hydroxylated: delphinidin, petunidin, malvidin) (Castellarin et al, 2007a;Ollé et al, 2011;Cook et al, 2015). However, the changes in the anthocyanin profile in response to water deficit appear to be highly varietal dependent (Niculcea et al, 2014;Theodorou et al, 2019).…”
Section: Water Impact Of Vine Water Status On Phenolic Compoundsmentioning
confidence: 99%
“…Those positive effects are mainly observed when stress occurs during the second growth phase where synthesis of anthocyanins and of most flavor compounds takes place and the berry is the major carbon sink. Besides an overall increased accumulation of phenylpropanoids (Chorti et al, 2016;Koundouras, 2018) several studies show an alteration in composition of flavonoids and anthocyanins towards tri-hydroxylated anthocyanins (3′,4′,5′hydroxylated: delphinidin, petunidin, malvidin) (Castellarin et al, 2007a;Cook et al, 2015;Ollé et al, 2011) and some report increased proanthocyanidin concentration and polymerization in grape berry skins (Cáceres-Mella et al, 2017;Kyraleou et al, 2016), whereas others report higher catechin and total polyphenol concentration (Zsófi et al, 2014). Interestingly, the modulation of anthocyanin structure in response to water deficit appears to be highly varietal dependent (Niculcea et al, 2014;Theodorou et al, 2019).…”
Section: Impact Of Water Deficit On Berry Physiology and Compositionmentioning
confidence: 99%
“…In order to increase the level of objectivity associated with the polyphenol fingerprinting of red varieties, it was recently proposed the monitoring of some analytical parameters that characterize the berry skins of red grapes at technological maturity [17,22]; these parameters are responsible for the TPC in must and the resulting wines [66]. Under these circumstances, the focus is kept on the high concentration of anthocyanins and easily extractable tannins that are contained in grape skins, in comparison with the limited amounts of extractable tannins and lack of anthocyanins in the seeds [17,22].…”
Section: Profiling Applicationsmentioning
confidence: 99%